Intraoperative trypan blue central landmark and its use in capsulotomy and capsulorhexis centration - Stodulka, Pavel; Packard, Richard; Mordaunt, David (Journal of cataract and refractive surgery, 2024)
PURPOSE: To compare 3 capsulotomy centration methods. SETTING: Private clinic, Zlin, Czech Republic. DESIGN: Prospective, consecutive case series. METHODS: 180 eyes undergoing cataract surgery had anterior capsule staining with microfiltered 0.4% trypan blue solution before selective laser capsulotomy. The first 60 eyes (Group 1) had mydriatic dilated pupil centered capsulotomies. The next 60 eyes (Group 2) were centered on the trypan blue central landmark (TCL). The final 60 capsulotomies (Group 3) were centered on the patient fixated coaxial Purkinje reflex (CPR). Measurements between key anatomical landmarks and the TCL, CPR capsulotomies, and implanted intraocular lens (IOL) center were made. RESULTS: The TCL, observed in >94% of eyes in the study, coincided with the CPR with a displacement of <0.1 ± 0.1 mm. Group 1 capsulotomies were noticeably decentered on the IOLs by 0.3 ± 0.2 mm. The Group 2 symmetrical IOL relationship was maintained with a decentration of 0.15 ± 0.1 mm. Group 3 had a similar decentration with the IOLs with 0.15 ± 0.1 mm. Verification with IOLMaster 700 data and CALLISTO Eye System showed that the CPR and the TCL were coincident with the measured visual axis. CONCLUSIONS: The clearly visible TCL served as an alternate landmark to the patient fixated CPR, and being on the anterior capsule was not sensitive to tilt. Further patient compliance was not required. Both were superior to dilated pupil centration, to achieve symmetric IOL coverage. This has application for both capsulotomies and capsulorhexes.
Keywords: trypanová modř; přední pouzdro oční čočky; Female; Trypan Blue; Anterior Capsule of the Lens; ženské pohlaví; fakoemulzifikace; lidé; Coloring Agents; pouzdro oční čočky; Phacoemulsification; Aged, 80 and over; anatomická značka; Anatomic Landmarks; prospektivní studie; Male; Capsulorhexis; capsulorhexis; Prospective Studies; Aged; barvicí látky; Lens Implantation, Intraocular; Lens Capsule, Crystalline; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; implantace nitrooční čočky; Middle Aged; Humans